The Direct Product of Hypermodules over a Hyperring - FatimahAlzahra Alqabaeli,; AbouElwan, Yasser; Hussein Shat, (AlQalam Journal of Medical and Applied Sciences, 2025)
The purpose of this work is studying the direct product of hypermodules. We introduce a general definition of the direct product of R-hypermodules by extending the classical coordinatewise construction from module theory. It is shown that the direct product preserves the axioms of an R-hypermodule. This result helped us to prove that, direct Product of R-hypermodules is an R-hypermodule, and that the canonical projections as hyperhomomorphisms.